Factors influencing the lifestyle of patients in the diabetes and hypertension club (Salud, Arte y Cuidado, 2020)
Objective: To determine the factors that influences the lifestyle of diabetic patients of the Diabetes and Hypertension Club of the Type III Urban Ambulatory "Antonio María Sequera Alcina". Tamaca. Barquisimeto. Lara State. Methods: This study is located in a quantitative, non-experimental method, supported by a descriptive field design. The population consisted of 110 patients, all over the age of 18 of both sexes, who met the respective conditions, with logical and rational mental functioning; they attend the diabetes and hypertension club every Tuesday. For the selection of the sample, the simple random sampling method made up of 22 patients was used. As a technique, the interview was used and a survey-type instrument structured by 4 dimensions was used, which corresponds to sociodemographic data, lifestyle, complications and healthy patterns, to respond to 25 items, which has to do with a Likert-type scale.  Conclusions: the way in which daily life is carried out has greatly influenced the diabetic patients studied, however, it was evidenced that several topics related to pathology are ignored as teaching / learning topics, which represents a deficit in the bases of knowledge of pathology, thus producing "healthy" inertia skills, as each patient believes in himself that it is the best way. The most common complications are produced by the bad habits that most have, which are not only marked by educational activities, but also physical, psychological, spiritual and even socializing attitudes
Keywords: Lifestyles; needs; care